7
$\begingroup$

How to prove the following two sums

\begin{align} \sum_{n=1}^\infty\frac{H_nH_n^{(2)}}{n^22^n}&=2\operatorname{Li}_5\left(\frac12\right)+\ln2\operatorname{Li}_4\left(\frac12\right)-\frac{31}{32}\zeta(5)+\frac{1}{8}\ln2\zeta(4)+\frac18\zeta(2)\zeta(3)\\&\quad-\frac{1}{12}\ln^32\zeta(2)+\frac{1}{40}\ln^52 \end{align}

\begin{align} \sum_{n=1}^\infty\frac{H_n^3}{n^22^n}&=-14\operatorname{Li}_5\left(\frac12\right)-9\ln2\operatorname{Li}_4\left(\frac12\right)+\frac{279}{16}\zeta(5)-\frac{25}{4}\ln2\zeta(4)-\frac78\zeta(2)\zeta(3)\\&\quad-\frac74\ln^22\zeta(3)+\frac{13}{12}\ln^32\zeta(2)-\frac{31}{120}\ln^52 \end{align} where $H_n^{(p)}=1+\frac1{2^p}+\cdots+\frac1{n^p}$ is the $n$th generalized harmonic number of order $p$ and $\operatorname{Li}_s(x)=\sum_{n=1}^\infty\frac{x^n}{n^s}$ is the polylogarithmic function.

Edit: These two sums were proposed by Cornel Ioan Valean here but no solution was submitted. I am presenting my solution in the answer section and would like to see different approaches.

Thanks.

$\endgroup$
7
$\begingroup$

I am going to use the following results :

$$V_1=\sum_{n=1}^\infty\frac{(-1)^nH_n^{(4)}}{n}=\frac78\ln2\zeta(4)+\frac38\zeta(2)\zeta(3)-2\zeta(5)$$

$$V_2=\int_0^{1/2}\frac{\ln^3(1-x)}{x(1-x)}\ dx=6\operatorname{Li}_4\left(\frac12\right)-6\zeta(4)+\frac{21}{4}\ln2\zeta(3)-\frac32\ln^22\zeta(2)+\frac14\ln^42$$

$$V_3=\int_0^{1/2}\frac{\ln^3(1-x)\ln x}{x(1-x)} dx=-12\operatorname{Li}_5\left(\frac12\right)-12\ln2\operatorname{Li}_4\left(\frac12\right)+\frac{285}{16}\zeta(5)-3\zeta(2)\zeta(3)$$

$$-\frac{21}{4}\ln^22\zeta(3)+2\ln^32\zeta(2)-\frac25\ln^52$$

$$V_4=\sum_{n=1}^\infty\frac{H_n^{(3)}}{n^22^n}=4\operatorname{Li}_5\left(\frac12\right)+3\ln2\operatorname{Li}_4\left(\frac12\right)-\frac{81}{64}\zeta(5)+\frac{5}{16}\ln2\zeta(4)-\frac78\zeta(2)\zeta(3)$$ $$+\frac78\ln^22\zeta(3)-\frac{5}{12}\ln^32\zeta(2)+\frac{11}{120}\ln^52$$


We are going to establish two relations and solve them by eliminations

The first relation:

From here we have

$$-\int_0^1x^{n-1}\ln^3(1-x)\ dx=\frac{H_n^3+3H_nH_n^{(2)}+2H_n^{(3)}}{n}$$

Multiply both sides by $\frac{1}{n2^n}$ then sum both sides from $n=1$ to $\infty$ we get

$$\sum_{n=1}^\infty\frac{H_n^3+3H_nH_n^{(2)}+2H_n^{(3)}}{n^22^n}=-\int_0^1\frac{\ln^3(1-x)}{x}\sum_{n=1}^\infty\frac{(x/2)^n}{n}=\int_0^1\frac{\ln^3(1-x)\ln(1-x/2)}{x}\ dx\\\overset{x\mapsto 1-x}{=}\int_0^1\frac{\ln^3x\ln\left(\frac{1+x}{2}\right)}{1-x}\ dx=-6\sum_{n=1}^\infty\frac{(-1)^nH_n^{(4)}}{n}=-6V_1$$

Note that for the last step, we used this rule $\int_0^1\frac{\ln^ax\ln(1+x)}{1-x}\ dx=(-1)^aa!\left(\ln2\zeta(a+1)+\sum_{n=1}^\infty\frac{(-1)^nH_n^{(a+1)}}{n}\right)$

Then

$$R_1=\sum_{n=1}^\infty\frac{H_n^3+3H_nH_n^{(2)}+2H_n^{(3)}}{n^22^n}=-6V_1$$


The second relation:

From here we have

$$-\frac{\ln^3(1-x)}{1-x}=\sum_{n=1}^\infty x^n\left(H_n^3-3H_nH_n^{(2)}+2H_n^{(3)}\right)\tag{1}$$

Divide both sides of (1) by $x$ then integrate from $x=0$ to $1/2$ and use the fact that $\int_0^{1/2}x^{n-1}\ dx=\frac1{n2^n}$ to get

$$\sum_{n=1}^\infty\frac{H_n^3-3H_nH_n^{(2)}+2H_n^{(3)}}{n2^n}=-\int_0^{1/2}\frac{\ln^3(1-x)}{x(1-x)}\ dx=-V_2$$

Now multiply both sides of (1) by $-\frac{\ln x}{x}$ then integrate from $x=0$ to $1/2$ and use that fact that $-\int_0^{1/2}x^{n-1}\ln x\ dx=\frac{\ln2}{n2^n}+\frac1{n^22^n}$ to get

$$\sum_{n=1}^\infty\left(H_n^3-3H_nH_n^{(2)}+2H_n^{(3)}\right)\left(\frac{\ln2}{n2^n}+\frac1{n^22^n}\right)=\int_0^{1/2}\frac{\ln^3(1-x)\ln x}{x(1-x)}\ dx=V_3$$

$$-\ln2V_2+\sum_{n=1}^\infty\frac{H_n^3-3H_nH_n^{(2)}+2H_n^{(3)}}{n^22^n}=V_3$$

Then

$$R_2=\sum_{n=1}^\infty\frac{H_n^3-3H_nH_n^{(2)}+2H_n^{(3)}}{n^22^n}=V_3+\ln2V_2$$


Now we are ready to calculate our sums and lets start with the first one:

$$\sum_{n=1}^\infty\frac{H_nH_n^{(2)}}{n^22^n}=\frac{R_1-R_2}{6}=-\frac{6V_1+\ln2V_2+V_3}{6}$$

and by plugging the results of $V_1$, $V_2$ and $V_3$ we get

\begin{align} \sum_{n=1}^\infty\frac{H_nH_n^{(2)}}{n^22^n}&=2\operatorname{Li}_5\left(\frac12\right)+\ln2\operatorname{Li}_4\left(\frac12\right)-\frac{31}{32}\zeta(5)+\frac{1}{8}\ln2\zeta(4)+\frac18\zeta(2)\zeta(3)\\&\quad-\frac{1}{12}\ln^32\zeta(2)+\frac{1}{40}\ln^52 \end{align}


As for the second sum :

$$\sum_{n^1}^\infty\frac{H_n^3}{n^22^n}=\frac{R_1+R_2}{2}=\frac{-6V_1+\ln2V_2+V_3-4V_4}{2}$$

and by plugging the results of $V_1$, $V_2$, $V_3$ and $V_4$ we get

\begin{align} \sum_{n=1}^\infty\frac{H_n^3}{n^22^n}&=-14\operatorname{Li}_5\left(\frac12\right)-9\ln2\operatorname{Li}_4\left(\frac12\right)+\frac{279}{16}\zeta(5)-\frac{25}{4}\ln2\zeta(4)-\frac78\zeta(2)\zeta(3)\\&\quad-\frac74\ln^22\zeta(3)+\frac{13}{12}\ln^32\zeta(2)-\frac{31}{120}\ln^52 \end{align}

.


Proofs of the results:

$V_1$ can be found here and $V_2$ can be found using wolfram but here is the steps

\begin{align} V_2&=\int_0^{1/2}\frac{\ln^3(1-x)}{x(1-x)}\ dx\overset{x\mapsto 1-x}{=}\int_{1/2}^1\frac{\ln^3x}{x(1-x)}\ dx\\ &=\int_{1/2}^1\frac{\ln^3x}{x}\ dx+\int_{1/2}^1\frac{\ln^3x}{1-x}\ dx\\ &=-\frac14\ln^42+\sum_{n=1}^\infty \int_{1/2}^1x^{n-1}\ln^3x\ dx, \quad \text{apply integration by parts}\\ &=-\frac14\ln^42+\sum_{n=1}^\infty\left(\frac{\ln^32}{n2^n}+\frac{3\ln^22}{n^22^n}+\frac{6\ln2}{n^32^n}+\frac{6}{n^42^n}-\frac{6}{n^4}\right)\\ &=-\frac14\ln^42+\ln^42+3\ln^22\operatorname{Li}_2\left(\frac12\right)+6\ln2\operatorname{Li}_3\left(\frac12\right)+6\operatorname{Li}_4\left(\frac12\right)-6\zeta(4)\\ &\boxed{=6\operatorname{Li}_4\left(\frac12\right)-6\zeta(4)+\frac{21}{4}\ln2\zeta(3)-\frac32\ln^22\zeta(2)+\frac14\ln^42} \end{align}

where we used $\operatorname{Li}_2\left(\frac12\right)=\frac12\zeta(2)-\frac12\ln^22$ and $\operatorname{Li}_3\left(\frac12\right)=\frac78\zeta(3)-\frac12\ln2\zeta(2)+\frac16\ln^32$


\begin{align} V_3&=\int_0^{1/2}\frac{\ln^3(1-x)\ln x}{x(1-x)}\ dx\overset{x\mapsto 1-x}{=}\int_{1/2}^{1}\frac{\ln^3x\ln(1-x)}{x(1-x)}\ dx\\ &=-\sum_{n=1}^\infty H_n\int_{1/2}^1 x^{n-1}\ln^3x\ dx\\ &=-\sum_{n=1}^\infty H_n\left(\frac{\ln^32}{n2^n}+\frac{3\ln^22}{n^22^n}+\frac{6\ln2}{n^32^n}+\frac{6}{n^42^n}-\frac{6}{n^4}\right)\\ &=-\ln^32\sum_{n=1}^\infty\frac{H_n}{n2^n}-3\ln^22\sum_{n=1}^\infty\frac{H_n}{n^22^n}-6\left(\color{blue}{\ln2\sum_{n=1}^\infty\frac{H_n}{n^32^n}+\sum_{n=1}^\infty\frac{H_n}{n^42^n}}\right)+6\sum_{n=1}^\infty\frac{H_n}{n^4} \end{align}

I managed here to prove

$$\color{blue}{\ln2\sum_{n=1}^\infty\frac{H_n}{n^32^n}+\sum_{n=1}^\infty\frac{H_n}{n^42^n}}=-\frac12\ln^22\sum_{n=1}^\infty\frac{H_n}{n^22^n}-\frac16\ln^32\sum_{n=1}^\infty\frac{H_n}{n2^n}+\frac12\sum_{n=1}^\infty\frac{H_n}{n^4}-\frac{47}{32}\zeta(5)+\frac1{15}\ln^52+\frac13\ln^32\operatorname{Li}_2\left(\frac12\right)+\ln^22\operatorname{Li}_3\left(\frac12\right)+2\ln2\operatorname{Li}_4\left(\frac12\right)+2\operatorname{Li}_5\left(\frac12\right)$$

and $V_3$ simplifies into

$$\small{V_3=3\sum_{n=1}^\infty\frac{H_n}{n^4}+\frac{141}{16}\zeta(5)-\frac25\ln^52-2\ln^32\operatorname{Li}_2\left(\frac12\right)-6\ln^22\operatorname{Li}_3\left(\frac12\right)-12\operatorname{Li}_4\left(\frac12\right)-12\operatorname{Li}_5\left(\frac12\right)} \\ \small{\boxed{=-12\operatorname{Li}_5\left(\frac12\right)-12\ln2\operatorname{Li}_4\left(\frac12\right)+\frac{285}{16}\zeta(5)-3\zeta(2)\zeta(3)-\frac{21}{4}\ln^22\zeta(3)+2\ln^32\zeta(2)-\frac25\ln^52\quad}}$$

where we substituted $\sum_{n=1}^\infty\frac{H_n}{n^4}=3\zeta(5)-\zeta(2)\zeta(3)$ along with the values $\operatorname{Li}_2\left(\frac12\right)$ and $\operatorname{Li}_3\left(\frac12\right)$.


To prove the last result of $V_4$, we use this generating function

$$\sum_{n=1}^\infty \frac{H_n^{(3)}x^n}{n}=\operatorname{Li}_4(x)-\ln(1-x)\operatorname{Li}_3(x)-\frac12\operatorname{Li}^2_2(x)$$

Divide both sides by $x$ then integrate from $x=0$ to $1/2$ and use the fact that $\int_0^{1/2} x^{n-1}\ dx=\frac1{n2^n}$ we get

\begin{align} V_4&=\int_0^{1/2}\frac{\operatorname{Li}_4(x)}{x}\ dx-\underbrace{\int_0^{1/2}\frac{\ln(1-x)\operatorname{Li}_3(x)}{x}\ dx}_{IBP}-\frac12\int_0^{1/2}\frac{\operatorname{Li}^2_2(x)}{x}\ dx\\ &=\operatorname{Li}_5\left(\frac12\right)+\operatorname{Li}_2\left(\frac12\right)\operatorname{Li}_3\left(\frac12\right)-\frac32\int_0^{1/2}\frac{\operatorname{Li}^2_2(x)}{x}\ dx \end{align}

@Song proved in this solution

$$\int_0^{1/2}\frac{\left(\operatorname{Li}_2(x)\right)^2}{x}\ dx=\frac12\ln^32\zeta(2)-\frac78\ln^22\zeta(3)-\frac58\ln2\zeta(4)+\frac{27}{32}\zeta(5)+\frac78\zeta(2)\zeta(3)\\-\frac{7}{60}\ln^52-2\ln2\operatorname{Li}_4\left(\frac12\right)-2\operatorname{Li}_5\left(\frac12\right)$$

by plugging this result along with the values of $\operatorname{Li}_2(1/2)$ and $\operatorname{Li}_3(1/2)$ the closed form of $V_4$ follows.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.